Early hypersynchrony in juvenile PINK1−/− motor cortex is rescued by antidromic stimulation - Carron, Romain; Filipchuk, Anton; Nardou, Romain; Singh, Abhinav; Michel, Francois J.; Humphries, Mark D.; Hammond, Constance (Frontiers in Systems Neuroscience, 2014)
In Parkinson’s disease, cortical networks show enhanced synchronized activity but whether this precedes motor signs is unknown. We investigated this question in PINK1-/- mice, a genetic rodent model of the PARK6 variant of familial Parkinson’s disease which shows impaired spontaneous locomotion at 16 months. We used two-photon calcium imaging and whole-cell patch clamp in slices from juvenile (P14-P21) wild-type or PINK1-/- mice. We designed a horizontal tilted cortico-subthalamic slice where the only connection between cortex and subthalamic nucleus (STN) is the hyperdirect cortico-subthalamic pathway. We report excessive correlation and synchronization in PINK1-/- M1 cortical networks 15 months before motor impairment. The percentage of correlated pairs of neurons and their strength of correlation were higher in the PINK1-/- M1 than in the wild type network and the synchronized network events involved a higher percentage of neurons. Both features were independent of thalamo-cortical pathways, insensitive to chronic levodopa treatment of pups, but totally reversed by antidromic invasion of M1 pyramidal neurons by axonal spikes evoked by high frequency stimulation (HFS) of the STN. Our study describes an early excess of synchronization in the PINK1-/- cortex and suggests a potential role of antidromic activation of cortical interneurons in network desynchronization. Such backward effect on interneurons activity may be of importance for HFS-induced network desynchronization.